86 Do all antiphospholipid antibodies confer the same risk for major organ involvement in systemic lupus erythematosus patients?. (April 2019) - Riancho-Zarrabeitia, Leyre; Martínez-Taboada, Víctor M; Figueroa, Iñigo Rua; Alonso, Fernando; Izquierdo, Maria Galindo; Ovalles-Bonilla, Juan; Olivé-Marqués, Alejandro; Nebro, Antonio Fernandez; Calvo, Jaime; Narváez-García, Javier; Muriel, Eva Tomero; Isacelaya, Esther Uriarte; et al.
Abstract : Background: Antiphospholipid antibodies (aPL) have been associated with organ damage and certain features in systemic lupus erythematosus (SLE) patients. Our aim is to investigate the association between the different aPL and SLE manifestations as well as to elucidate the influence of the load of antibodies. Methods: Patients from the RELESSER-T registry were included. RELESSER-T is a multicenter, hospital-based registry, with retrospective cross-sectional collection of data from a large representative sample of adult non-selected patients with SLE attending Spanish rheumatology services from the public national health system. Results: Out of a total of 3651 SLE patients, 1368 were positive for aPL (44.9% of patients were positive for anticardiolipin (aCL) antibodies, 27.3% for anti b2glycoprotein I (aB2GPI) and 24% for lupus anticoagulant (LA)). Regarding the load of antibodies, 20.6%, 12.1% and 4.8% were positive for one, two and three antibodies, respectively. The association between the different aPL, the number of positive antibodies and antiphospholipid syndrome related manifestations is showed in table 1 . Overall, all types of aPL were associated with classic APS manifestations, although LA, IgG isotypes, and patients with more than one aPL display a higher risk to develop clinical APS. Regarding specific lupus manifestations, all aPL types showed a negative association with cutaneous manifestations, and was also significantly associated with the load of autoantibodies (p<0.001). LA and aCL were associated with an increased risk of cardiac, respiratory and neuropsychiatric manifestations (p<0.001). Furthermore, LA was also associated with an increased risk of renal disease (p<0.001). aCL IgG was associated with a higher risk of specific lupus manifestations compared with aCL IgM. Interestingly, aB2GP IgG were only associated with an increased risk of seizures (p<0.001). When evaluating the influence of the load of antibodies, we found that the risk of neuropsychiatric manifestations (p<0.001), as well as the cardiac (p=0.003), and pulmonary manifestations (p=0.001), significantly increased with a higher number of positive antibodies. Inversely, the risk of cutaneous symptoms decreased while the number of positive antibodies increased (OR 0.89, 95% CI 0.82–0.96, p=0.003). Conclusions: The present study in a large SLE cohort confirm than there is a hierarchy for aPL and the risk of APS and lupus manifestations. aCL, and especially LA, confer a higher risk for major organ involvement in SLE patients. IgG isotypes and the load of aPL antibodies confer a higher risk for clinical APS and major lupus manifestations. Funding Source(s): None